Hipotiroidismo Subclínico no Idoso - Macedo Silva, S (2019)
Subclinical hypothyroidism, defined as an increase of thyroid stimulating hormone levels with normal levels of thyroid hormones, could have a multiorgan impact. There seem to be differences in the elderly (over 65 years of age) which indicate that there should be a different approach in terms of diagnosis and the treatment.